A Patient With Thiamine Deficiency Exhibiting Muscle Edema Suggested by MRI - Murate, Kenichiro; Mizutani, Yasuaki; Maeda, Toshiki; Nagao, Ryunosuke; Kikuchi, Kouichi; Shima, Sayuri; Niimi, Yoshiki; Ueda, Akihiro; Ito, Shinji; Mutoh, Tatsuro (Frontiers in Neurology, 2018)
Myalgia is sometimes observed in patients with thiamine-deficiency neuropathy. However, the detailed mechanism(s) underlying muscular manifestations have been poorly elucidated. We herein report a possible patient with thiamine-deficiency neuropathy exhibiting muscle weakness and myalgia in lower limbs. The patient exhibited abnormal muscle signal intensities on MRI corresponding to the site of myalgia. After thiamine replacement therapy, rapid improvement of clinical symptoms and abnormal MRI findings were observed. Muscle MRI findings in this case implicated the possible mechanism of myalgia observed in patients with thiamine deficiency neuropathy.